Methodology For Evaluating Investment Projects Under Uncertainty - Avag Simonyan (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
This paper examines contemporary approaches to evaluating investment projects under conditions of uncertainty. It centers on the mathematical formalization of discounted cash-flow and annuity methods, and on their integration with sensitivity analysis and stress-testing frameworks. The study justifies the need for an integrated model that accounts for asymmetric project perceptions as well as a range of additional risk factors influencing financial outcomes. Practical feasibility is demonstrated through the use of programmable spreadsheets, enabling flexible parameterization and rapid updating of inputs. The results not only facilitate an objective assessment of a project’s investment appeal but also yield concrete risk-management recommendations, thereby enhancing project resilience in a dynamic economic environment. This work will interest researchers, graduate students and practitioners in finance and investment analysis who seek to fuse theoretically sound models with empirical evaluation to derive robust strategic decisions under market uncertainty. Moreover, the paper offers value to academics and executives engaged in interdisciplinary research aimed at critically refining and optimizing investment appraisal techniques through advanced econometric and mathematical methods.